A molecular genetic investigation of schizophrenia in an Irish study population - Corvin, Aiden (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2006)
Schizophrenia (OMIM 181500) is a complex genetic disorder, which affects ~1% of the population, and typically presents in early adulthood with abnormalities of perception (psychosis), cognition, information processing and social functioning. Genetic epidemiological research suggests that schizophrenia is related to other psychotic disorders (including schizoaffective disorder and bipolar affective disorder). As a group these functional psychoses are chronic in course, and associated with substantial morbidity. Current treatments are partially effective and were discovered surreptitiously: establishing genes that contribute to these disorders may be important in understanding the biology involved and developing new therapies.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin